A New Look at the Victorian ‘Criminal Classes’: A View from the Archives - Philippe Chassaigne (Cahiers Victoriens et Edouardiens)
Much has been said—and written—about the Victorian ‘dangerous classes’. In particular, interpreting the adoption of repressive legislation in the wake of the 1860s ‘moral panics’ (1863 Garotters’ Act, 1864 Penal Servitude Act, 1869 and 1871 Habitual Criminals Acts) as a means for the ruling middle classes of comforting and legitimising their political and social hegemony by labelling certain inferior social groups as a ‘criminal class’ (or ‘underclass’, or ‘residuum’) and making them the target of police and justice repression, has proved to be a particularly popular and enduring line of thought (see Jennifer Davis et alii). This paper argues that a closer look at the judicial archives shows a somewhat different picture. It assesses to what extent this tougher line on crime and violence suggested by the adoption of repressive legislation was actually implemented, and which social groups, if any, were effectively the targets of this repression. It then considers the actual meaning of this rhetoric about the ‘dangerous classes’: a strengthening of social control, or a promotion of social cohesion?